2014
DOI: 10.1179/2045772314y.0000000234
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriology of pressure ulcers in individuals with spinal cord injury: What we know and what we should know

Abstract: Individuals with spinal cord injury (SCI) are at increased risk for the development of pressure ulcers. These chronic wounds are debilitating and contribute to prolonged hospitalization and worse medical outcome. However, the species of bacteria and the role that specific species may play in delaying the healing of chronic pressure ulcers in the SCI population has not been well characterized. This study will review the literature regarding what is known currently about the bacteriology of pressure ulcers in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
58
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 78 publications
(131 reference statements)
8
58
0
6
Order By: Relevance
“…16 In a recent review article, Dana and Bauman stated that the most common organisms found in pressure ulcers are S. aureus, Proteus mirabilis, P. aeruginosa, and E. faecalis. 17 With the exception of E. coli, all of the microbes isolated in the reviewed wound studies, excluding E. coli, were also found within the foam dressing extracts in this study. The most commonly identified microbes in these wounds were Staphylococcus (27), Corynebacterium (7), Enterococcus (7), Pseudomonas (5) Streptococcus (3), and Klebsiella.…”
Section: Discussionmentioning
confidence: 57%
“…16 In a recent review article, Dana and Bauman stated that the most common organisms found in pressure ulcers are S. aureus, Proteus mirabilis, P. aeruginosa, and E. faecalis. 17 With the exception of E. coli, all of the microbes isolated in the reviewed wound studies, excluding E. coli, were also found within the foam dressing extracts in this study. The most commonly identified microbes in these wounds were Staphylococcus (27), Corynebacterium (7), Enterococcus (7), Pseudomonas (5) Streptococcus (3), and Klebsiella.…”
Section: Discussionmentioning
confidence: 57%
“…Other gram-negative organisms and anaerobic bacteria can cause polymicrobial septic arthritis complicating soft tissue infections, most commonly in neuropathic individuals with pressure ulcers, due to spinal cord injury [51]. Patients with ischemic limbs or chronic ulcers due to chronic venous insufficiency or arterial insufficiency may also have polymicrobial septic arthritis of the ankle or knee caused by gram-negative and anaerobic organisms in addition to staphylococci and streptococci [52].…”
Section: Microbiologymentioning
confidence: 99%
“…W przeglądzie Dana i Bauman obejmującym dane pochodzące z badań przeprowadzonych wśród pacjentów po urazie rdzenia kręgowego od 1966 do 2014 roku zidentyfikowano 52 gatunki bakterii, z czego ponad połowę stanowiły bakterie beztlenowe [16].…”
Section: Dane Mikrobiologiczneunclassified
“…Ogólnie najczęściej identyfikowanymi mikroorganizmami są: Staphylococcus aureus, Staphylococcus epidermidis, Proteus mirabilis, Pseudomonas aeruginosa oraz Escherichia coli, Acinetobacter, Providencia, Klebsiella [16]. W sytuacji gdy doszło do przerwania ciągłości skóry, przewlekłe rany mogą być kolonizowane przez bakterie pochodzące ze środowiska zewnętrznego, przylegających fragmentów skóry, przewodu pokarmowego i błony śluzowej układu moczowo-płciowego [16].…”
Section: Dane Mikrobiologiczneunclassified
See 1 more Smart Citation